Developmental Assets, Self-Control and Internet Gaming Disorder in Adolescence: Testing a Moderated Mediation Model in a Longitudinal Study - Xiang, Guo-Xing; Gan, Xiong; Jin, Xin; Zhang, Yan-Hong; Zhu, Cong-Shu (Frontiers in Public Health, 2022)
Internet gaming disorder (IGD) is gradually becoming an important social problem among worldwide youth and has been included in the eleventh International Classification of Diseases (ICD-11). The present study determined to investigate the relationship of developmental assets, self-control and IGD. A two-wave longitudinal study, with each wave spanning half year apart, was conducted in a sample of 1023 adolescents (aging from 11 to 15, 49.36% boys). Results of moderated mediation model revealed that T1 developmental assets could predict less IGD at T2 directly, or through T1 self-control indirectly. Besides, T1 self-control partly mediated the association in the man group, while it completely mediated the relation in the woman group. The prevention and intervention for adolescent IGD are discussed.